Dopant Free Triphenylamine‐Based Hole Transport Materials with Excellent Photovoltaic Properties for High‐Performance Perovskite Solar Cells. Issue 2 (8th December 2021) - Naeem, Naila; Shehzad, Rao Aqil; Ans, Muhammad; Akhter, Mohammed Salim; Iqbal, Javed
Abstract : Recently, scientists are more devoted to designing and synthesizing organic perovskite solar cells for attaining high power conversion efficiency (PCE). Herein, a series of small molecules as hole transport materials with A–π–D–π–A framework, namely (DFA1, DFA2, DFA3, and DFA4 ) having triphenylamine (TPA)‐based central donor core unit (A1–A4 ) end‐capped acceptor moieties linked via thiophene spacer is designed theoretically to study optoelectronic and photovoltaic properties. MPW1PW91 hybrid functional in conjunction with 6‐31G** basis set is found the best method to investigate the optoelectronic and photovoltaic properties. All hole transport materials (HTMs) possess a high open‐circuit voltage (0.98–1.41 V) with downshifted highest occupied molecular orbital energy values (−4.98 to −5.41 eV) by tailoring of electron‐withdrawing acceptor moieties. Meanwhile, appropriate elongation of π‐conjugated acceptor units is advantageous for enhancing the molar absorption coefficient and intermolecular electronic coupling. The highest hole mobility and charge transfer integral owing to lower hole reorganization energies indicate these molecules are best for HTMs. DFA1‐DFA4 has a power conversion efficiency of up to 24% which authenticates that these HTMs have excellent photovoltaic attributes compared to the reported reference DFH. The present computational investigation validates the efficacy of the designed techniques and opens a new route for designing high‐performance dopant‐free HTMs in perovskite solar cells. Abstract : Series of hole transport materials (DFA1 –DFA4 ) with framework A–π–D–π–A having a central donor (D) core, end‐capped acceptor (A) unit linked via thiophene π‐spacer were simulated by MPW1PW91/6‐31G**. Optoelectronic and photovoltaic properties of designed molecules are evaluated with respect to DFH by modification of electron withdrawing acceptor units on the efficiency of hole‐transport materials (HTMs). All HTMs have excellent power conversion efficiency up to 24.25%.